Cryptogenic strokes and neurological symptoms of Fabry disease - Ruiz-Franco, Maria Luisa; Vélez-Gómez, Beatriz; Martínez-Sánchez, Patricia; Garófano-López, Remedios; Gómez-Navarro, Carlos; Arjona-Padillo, Antonio (Frontiers in Neurology, 2025)
IntroductionFabry disease (FD) is the second most common lysosomal storage disorder. It mainly affects young people. FD can be characterized by neurological symptoms that can occur in both the central and peripheral nervous systems. Cerebrovascular involvement is common in FD and is considered an important cause of cryptogenic strokes. This study aimed to describe the neurological symptoms in patients with FD in general and, specifically, to determine the frequency of association between this disease and cerebrovascular manifestations in our environment.Materials and methodsThis retrospective, observational, cross-sectional study included all patients in the FD registry of the nephrology and cardiology Departments of our center. A descriptive analysis of demographic, neurological, clinical, and neuroimaging variables was performed, with a particular focus on their association with stroke or other cerebrovascular events prior to diagnosis.ResultsA total of 25 patients were included, with 14 (68%) of them being women. The median age of the patients was 52 years (relative intensity of collaboration [RIC] = 24.5). The patients belonged to five families with specific galactosidase alpha gene (GLA) mutations. Neuroimaging was performed in 13 (52%) patients, most of whom did not have neurological symptoms but had normal imaging results. Only 2 (8%) patients had nonspecific white matter hyperintensities. Among the 11 (44%) patients with neurological involvement, the most common symptom was pain in the extremities (32%). Stroke was identified in only one patient (4%), which occurred prior to the diagnosis of FD and was determined to be of cardioembolic etiology.DiscussionFD is found to be associated with several neurological symptoms. In our study, the most common neurological symptom was limb pain, which had varied characteristics. On the other hand, the incidence of stroke was significantly lower than that expected.